Experience with Pediatric Kidney Transplantation, 1985-2016: A Single Regional Center Study - Min, So Yoon; Jo, Tae Kyoung; Baek, Hee Sun; Park, Sook-Hyun; Kim, Hyung-Kee; Huh, Seung; Cho, Min Hyun (Childhood kidney diseases, 2017)
Purpose Kidney transplantation (KT) is an ideal treatment for pediatric patients with end-stage renal disease (ESRD). We report the clinical outcomes of pediatric ESRD patients who underwent KT in a single regional center. Methods We retrospectively investigated the medical records of 60 pediatric patients who were diagnosed with ESRD and underwent KT in our hospital between January 1985 and June 2016. Results A total of 60 children and adolescents (40 male, 20 female; mean age, 13.86±4.26 years) were included in this study. Six patients (10.0%) underwent KT immediately after receiving the diagnosis of ESRD, while the others underwent KT after dialysis treatment (mean period of dialysis, 368.7±4,41.8 days). The mean donor age (50 living-related [83.3%], 10 deceased [16.7%]) was 40.0±12.85 years and the male:female ratio was 1.07:1. The most common cause of ESRD was chronic glomerulonephritis. The overall survival rates at 1, 3, and 5 years after KT were 98%, 98%, and 96%, respectively, while the graft survival rates at 1, 3, and 5 years were 93%, 86%, and 68%, respectively. Children who underwent KT before 10 years of age had better monthly growth rates than those who underwent KT later than 10 years of age. Conclusions KT is performed less frequently in children than in adults, but causes of ESRD vary and clinical outcomes after KT greatly affect the growth and development of pediatric patients. Therefore, further analysis and monitoring of clinical progression after KT in pediatric ESRD patients are necessary.